Neighborhood Indicators of Employment and Economic Family Well-Being for Zipcode 53206 - (:unkn) unknown (My University, 2006)
This report assesses employment, economic and welfare changes in Milwaukee ZIP code 53206 based on thirteen years of institutional data. Recently released Census 2000 transportation planning databases are used to provide a first-time analysis by race of jobs located within each central city neighborhood. State-of-the art purchasing power and retail sales leakage analyses developed by the Employment and Training Institute help communities and neighborhood-based businesses assess the spending power of each central city zipcode. The 2004 income tax analyses (based on state tax returns filed in 2005) provide income data that is five years more current than the 1999 incomes reported by the 2000 Census.
Keywords: neighborhood indicators; community assets